Lower extremity joint loading in carved ski and snowboard turns - Klous, M.; Müller, E.; Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Skiing and snowboarding are the most popular winter sports in the Alps and are practiced by an increasing number of people. With the increasing number of practitioners, also the number of injuries increased. In skiing, most injuries are located in the lower extremities and in snowboarding about 1/3 of all injuries involve the lower extremities. To improve safety aspects in skiing and snowboarding, more knowledge is required about loading on the lower extremities joints. In the current paper, the loading at the knee and ankle joint in skiing and snowboarding are compared. Results showed that loading is more evenly distributed between the legs in snowboarding. Furthermore, the highest average and resultant peak forces at the knee were found in the outside leg in skiing. The highest forces at the ankle joint were observed at the outside leg in skiing, whereas the largest moments were found in the rear leg in snowboarding.